Prolonged Rest, Long-Term Dynamic Balance, and Gait in a Mouse Ankle-Sprain Model - Wikstrom, Erik A. (J Athl Train, 2019)
CONTEXT: Lateral ankle sprains (LASs) result in short- and long-term adaptations in the sensorimotor system that are thought to contribute to the development of chronic ankle instability and posttraumatic ankle osteoarthritis. Debate continues as to the appropriateness of rapid return to sport after LASs given the prevalence of long-term consequences. OBJECTIVE: To examine the short- and long-term effects of prolonged rest, as a model of immobilization, on dynamic balance and gait outcomes after a severe LAS in a mouse model. DESIGN: Controlled laboratory study. SETTING: Research laboratory. INTERVENTION(S): At 7 weeks of age, 18 male mice (CBA/J) had their right anterior talofibular and calcaneofibular ligaments transected. Mice were then randomized to 1 of 3 groups representing when access to a running wheel postsurgery was gained: at 3 days, 1 week, and 2 weeks. MAIN OUTCOME MEASURE(S): Dynamic balance and spatial gait characteristics were quantified before surgery (baseline) and at 3 days and 1, 2, 4, 6, 12, 18, 24, 30, 36, 42, 48, and 54 weeks postinjury. RESULTS: Relative to prolonged rest, resting for only 3 days resulted in worse dynamic balance during the later assessment points (42–54 weeks postinjury, P < .01). Mice that underwent a prolonged rest period of 2 weeks crossed the balance beam faster than the group that rested for only 3 days when averaged across all time points (P < .012). Spatial gait characteristics did not differ among the groups (P > .05). CONCLUSIONS: Relative to 3 days of rest, prolonged rest (1 and 2 weeks) after a severe LAS in mice positively affected balance. The apparent benefit of prolonged rest was noted on both dynamic-balance outcomes and performance. Stride length was not altered by the duration of rest after a surgically induced severe LAS in mice. Future research is needed to determine if these results translate to a human model.